Initiating venetoclax treatment: Clinical practice pearls (Canadian Hematology Today, 2023)
Overexpression of BCL-2 has been demonstrated in chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) cells where it mediates tumor cell survival and has been associated with resistance to chemotherapeutics. Venetoclax is a selective and orally bioavailable small- molecule inhibitor of BCL-2, an anti-apoptotic protein. Based on evidence demonstrating improvement in progression-free survival (PFS) and overall survival (OS), it has been approved in Canada for various regimens in the treatment of CLL and AML (i.e., venetoclax monotherapy, venetoclax/obinutuzumab and venetoclax/rituximab for CLL and venetoclax/azacitidine for AML). Initiation of venetoclax can be complicated as it requires ramp-up dosing with bloodwork and hydration to reduce the risk for tumor lysis syndrome (TLS). This article will focus on providing guidance during the initiation of venetoclax, particularly in resource limited centres.